1994
DOI: 10.1148/radiology.191.2.8153305
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arteries and lung parenchyma in chronic pulmonary embolism: preoperative and postoperative CT findings.

Abstract: CT enables demonstration of pulmonary thromboembolism with criteria pertaining to pulmonary arteries and to lung parenchyma and enables assessment of technical operatibility and confirmation of surgical success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…Similarly, Schwickert et al analyzed the CT findings in 75 patients diagnosed with CTEPH and found mosaic perfusion in 77% (34). However, the mosaic perfusion pattern can also be found in patients with PH due to other causes (31)(32)(33)(34)(35)(36)(37), and up to 12% of patients with idiopathic pulmonary arterial hypertension will have mosaic perfusion on CTPA (35).…”
Section: Mosaic Attenuation Patternmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Schwickert et al analyzed the CT findings in 75 patients diagnosed with CTEPH and found mosaic perfusion in 77% (34). However, the mosaic perfusion pattern can also be found in patients with PH due to other causes (31)(32)(33)(34)(35)(36)(37), and up to 12% of patients with idiopathic pulmonary arterial hypertension will have mosaic perfusion on CTPA (35).…”
Section: Mosaic Attenuation Patternmentioning
confidence: 97%
“…A report was considered as suggestive of chronic thromboembolic pulmonary disease if it stated visualization of the thrombus, calcified thrombus, recanalization, sudden change in vessel caliber, strictures, poststenotic dilatation, webs, or perfusion abnormality (30)(31)(32)(33)(34). The presence of mosaic perfusion, defined as areas of increased and decreased attenuation and vascularity without evidence of destruction or displacement of pulmonary vessels, was also noted.…”
Section: Multidetector Ctpamentioning
confidence: 99%
“…Eccentrically located, potentially calcified masses within the pulmonary arteries, contiguous to the vessel wall, abrupt cut-off of lobar or segmental arteries, and irregularities of the vessel diameter are considered findings suggestive of chronic PE ( fig. 4) [18].…”
Section: Image Interpretationmentioning
confidence: 99%
“…4,5 Anticoagulation with warfarin was considered the treatment of choice in our patient due to her extensive cardiac history. Her symptoms have largely resolved and she is now mobile.…”
Section: Discussionmentioning
confidence: 99%